2009
DOI: 10.1038/jhg.2008.7
|View full text |Cite
|
Sign up to set email alerts
|

New findings from genetic association studies of schizophrenia

Abstract: In the past 20 years, association studies of schizophrenia have evolved from analyses in lesser than 100 subjects of one or two markers in candidate genes to systematic analyses of association at a genome-wide level in samples of thousands of subjects. During this process, much of the emergent literature has been difficult to interpret and definitive findings that have met with universal acceptance have been elusive, largely because studies have been underpowered for such conclusions to be drawn. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 58 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…In a model free approach GWAS allow the identification of previously unsuspected genes and pathways in disease aetiology. Implementation of GWAS has brought considerable progress in the identification and robust replication of common gene variants that confer susceptibility to common diseases and other phenotypes of interest although these genetic effect-sizes are almost invariably moderate to small in magnitude [Lango and Weedon, 2008;Mullen et al, 2009;Williams et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In a model free approach GWAS allow the identification of previously unsuspected genes and pathways in disease aetiology. Implementation of GWAS has brought considerable progress in the identification and robust replication of common gene variants that confer susceptibility to common diseases and other phenotypes of interest although these genetic effect-sizes are almost invariably moderate to small in magnitude [Lango and Weedon, 2008;Mullen et al, 2009;Williams et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…These disorders have been shown to be highly heritable by monozygotic and dizygotic twin studies and by adoption studies: the heritability estimates for SCZ range from 70 to 85% and, for BD, from 60 to 85% 5 . Over the past two decades, genetic studies of thousands of samples have identified hundreds of candidate genes 6-8 . Most of these findings have not been supported by genome-wide studies.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of the disease is currently based on clinical criteria and lacks objective tests. Although there is much support for a genetic component in vulnerability to the illness, and a number of chromosome loci and candidate genes have been recognized, much about the genetic basis of schizophrenia remains unknown (for a recent review, see Williams and colleagues 1 ). Several genes are likely to contribute to susceptibility, and patterns of inheritance are intricate and irregular.…”
Section: Introductionmentioning
confidence: 99%